Climate change and its impact on animal distribution (Zoological Records and Reviews, 2024)
Climate change is reshaping the distribution of animal species at unprecedented rates, with documented range shifts,phenological mismatches, and altitudinal and latitudinal redistributions across taxa globally. This study quantifiesobserved and projected climate-driven distributional changes for thirty vertebrate species across five taxonomic groups(freshwater fish, amphibians, reptiles, breeding birds, and terrestrial mammals) in the Netherlands, Germany, and Spainusing long-term atlas data (1990-2023), species distribution models (MaxEnt), and CHELSA-CMIP6 climate projectionsunder SSP2-4.5 and SSP5-8.5 scenarios to 2050 and 2100. Observed range shifts over 1990-2023 were significant for22 of 30 species (73.3%), with a mean northward shift of 48.4 +- 12.1 km per decade across all groups (linear mixedmodel p < 0.001) and a mean upslope shift of 12.8 +- 4.1 m per decade for montane species. Thermophilous reptilesshowed the most pronounced range expansions (mean +124.4 km northward since 1990), while cold-adapted freshwaterfish showed the most severe range contractions (mean -38.4% suitable habitat area since 1990). MaxEnt SDMprojections under SSP5-8.5 predict that 64.0% of study species will lose > 20% of current suitable habitat by 2050, while28.0% are projected to gain suitable habitat through northward or upslope range expansion. Phenological data for eightbird species confirm advancing spring arrival dates (mean -5.8 +- 1.4 days per decade), creating measurablemismatches with invertebrate prey phenology at three study sites. These findings quantify the urgency ofclimate-adaptive conservation planning under the Kunming-Montreal GBF and EU Climate Adaptation Strategy.
Keywords: climate adaptation; breeding birds; reptiles; freshwater fish; SSP scenarios; phenological mismatch; MaxEnt; species distribution models; range shifts; climate change